DYNAMIC DESIGN OPTIMIZATION OF A TURBOPROP ENGINE VIBRATION ISOLATION SYSTEM - ZHANG Di; LI Jian; WEI Wei; MENG WeiHua; ZHANG HongXiao (Jixie qiangdu)
Aiming at the problem of vibration isolation design of turboprop engine single mounting surface vibration isolation mounting system, this paper proposes a method to optimize the stiffness parameters of the mounting system vibration isolator to achieve the vibration decoupling of the engine mounting system and the improvement of the vibration isolation efficiency. This paper takes a turboprop engine installation system as an example, uses this method to establish a six-degree-of-freedom installation system dynamics model, and combines the NSGA-Ⅱ genetic algorithm with the installation system dynamics analysis. While the vertical stiffness affects the design life, the multi-objective optimization of the vibration isolation efficiency and vibration decoupling of the installation system is realized. The optimization results show that the installation system has obtained high vibration isolation efficiency and vibration decoupling rate, and the comprehensive vibration isolation performance is good.